2012
DOI: 10.2337/db11-1275
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Hyperinsulinemia and Hyperglycemia Increase Myocardial Lipid Content in Normal Subjects

Abstract: Increased myocardial lipid content (MYCL) recently has been linked to the development of cardiomyopathy in diabetes. In contrast to steatosis in skeletal muscle and liver, previous investigations could not confirm a link between MYCL and insulin resistance. Thus, we hypothesized that cardiac steatosis might develop against the background of the metabolic environment typical for prediabetes and early type 2 diabetes: combined hyperglycemia and hyperinsulinemia. Therefore, we aimed to prove the principle that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 37 publications
4
42
1
Order By: Relevance
“…Similarly, in fasting conditions, glycogen depots tended to be lower and RPP was higher. In line with our findings, elevations in HR and RPP have been observed in patients with type 2 diabetes or those fed a high-fat diet [1,16] while no change in haemodynamic variables has been observed following an acute exposure to isolated hyperglycaemia [38] or combined hyperinsulinaemiahyperglycaemia [34].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similarly, in fasting conditions, glycogen depots tended to be lower and RPP was higher. In line with our findings, elevations in HR and RPP have been observed in patients with type 2 diabetes or those fed a high-fat diet [1,16] while no change in haemodynamic variables has been observed following an acute exposure to isolated hyperglycaemia [38] or combined hyperinsulinaemiahyperglycaemia [34].…”
Section: Discussionsupporting
confidence: 78%
“…Our results indicate that exposure to physiologically elevated NEFA levels may be a key mechanism in promoting TG accumulation in the myocardium, which appears to have a dynamic lipid depot that is responsive to acute metabolic changes [13,34]. Prolonged fasting (~20 h) was associated with a rise in plasma NEFA concentrations and appearance rates.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This indicates that MyLC 24 than that observed in previous studies of non-HF patients, and it is in accordance with findings of a high myocardial FFA uptake in case of impaired glucose tolerance. 35 FFA, triglyceride levels, and MyLC correlated positively.…”
Section: Short-term Modulation Of Mylc In Patients With T2d and Hfsupporting
confidence: 79%
“…Winhofer et al 24 report that hyperglycemic clamp and hyperinsulinemia cause an increase in MyLC in normal subjects. We found that MyLC was lowest during hyperinsulinemic-euglycemic clamping (low FFA).…”
Section: Study Limitationsmentioning
confidence: 99%